Are open and neurotic behaviors related to cognitive behaviors in daily life of older adults?. Issue 3 (25th July 2018) - Aschwanden, Damaris; Luchetti, Martina; Allemand, Mathias
Abstract: Objective: Previous research has shown a positive relationship between Openness and cognitive engagement as well as Neuroticism and cognitive complaints at the between‐person level. However, less is known about these associations at the within‐person level in daily life. Using daily assessments, the present study examined these associations both at the between‐person and within‐person level. Knowing the within‐person associations is important to provide valuable information for simple preventive and interceptive intervention strategies. Method: This study sampled 136 healthy older participants ( M  = 70.45 years; 41.2% male). Open and neurotic behaviors as well as cognitive engagement and complaints were measured every evening over 11 days. Results: The results of multilevel models showed a positive association between open behaviors and cognitive engagement at the between‐person and within‐person level. For neurotic behaviors and cognitive complaints, no association was found at either level of analysis. Conclusions: These findings extend previous research by providing the investigation of the associations between specific naturally occurring behaviors related to personality and cognition in the daily life of older adults at the within‐person level. Furthermore, these results may offer some basis for future intervention studies that should test whether a simple intervention aimed at promoting Openness‐related behaviors may increase cognitive engagement.